Potential Benefits of Implementing Building Information Modelling (BIM) in the Nigerian Construction Industry - Okereke, Reuben; Muhammed, Usman; Eze, Emmanuel (Journal of Technology Management and Business, 2021)
Building Information Modelling (BIM) is an innovative technology that has transformed the way construction projects are delivered. It has helped to overcome the problems of cost and time overruns, poor quality, safety issues, dissatisfaction, and loss of profit, among others; associated with the traditional method of project delivery. Despite the enormous benefits of BIM, its adoption and implementation among construction companies in the construction industry of developing nations remained low. In order to drive and influence the wider implementation of BIM, this study assessed the perceived potential benefits of BIM in the Nigerian construction industry. The study adopted a survey approach in which well-structured questionnaires were used to gather data from construction professionals in Port Harcourt, Nigeria, using snowball sampling techniques. With 132 responses, the data gathered were analysed using frequencies, percentile, relative importance index (RII) and Kruskal-Wallis test. The study concluded the level of awareness of BIM is high while its adoption is low. Also, the potential benefits of BIM adoption that could encourage wider implementation in construction are; improve project quality, minimize errors and mistakes, better clash detection, reduced construction time, improve multi-party communication and collaboration, improve project documentation, improves efficiency and productivity, project cost reduction, and minimizes disputes and conflicts. The Government of Nigeria and other African countries should come up with a policy that would make BIM application in construction mandatory.